2011
DOI: 10.1073/pnas.1100048108
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA signatures in tissues and plasma predict development and prognosis of computed tomography detected lung cancer

Abstract: The efficacy of computed tomography (CT) screening for early lung cancer detection in heavy smokers is currently being tested by a number of randomized trials. Critical issues remain the frequency of unnecessary treatments and impact on mortality, indicating the need for biomarkers of aggressive disease. We explored microRNA (miRNA) expression profiles of lung tumors, normal lung tissues and plasma samples from cases with variable prognosis identified in a completed spiral-CT screening trial with extensive fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
565
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 638 publications
(605 citation statements)
references
References 39 publications
22
565
2
6
Order By: Relevance
“…A negative result was found in 810 out of the 1067 (76%) individuals without lung cancer and in 10 of the 48 (21%) individuals with lung cancer, and the authors suggested that the miRNA test could be used as a first-line screening tool in high-risk individuals. However, the usefulness of miRNAs extends beyond the early detection of NSCLC [89,90]. miRNA panels offer the possibility to differentiate NSCLC from benign lesions and to determine the histological tumour type from a tissue sample [87,91], with sensitivities and specificities within the range of 60-100%.…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A negative result was found in 810 out of the 1067 (76%) individuals without lung cancer and in 10 of the 48 (21%) individuals with lung cancer, and the authors suggested that the miRNA test could be used as a first-line screening tool in high-risk individuals. However, the usefulness of miRNAs extends beyond the early detection of NSCLC [89,90]. miRNA panels offer the possibility to differentiate NSCLC from benign lesions and to determine the histological tumour type from a tissue sample [87,91], with sensitivities and specificities within the range of 60-100%.…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
“…miRNA panels offer the possibility to differentiate NSCLC from benign lesions and to determine the histological tumour type from a tissue sample [87,91], with sensitivities and specificities within the range of 60-100%. In their analysis, Boeri et al [89] suggested that specific miRNAs detectable in plasma samples collected from healthy smokers with an average exposure of 40 pack-years allowed the identification of those with NSCLC 1-2 years before the first symptoms of lung cancer became evident and allowed determination of their prognoses. Cazzoli et al [92] screened 742 miRNAs isolated from circulating exosomes and identified four miRNAs (miR-378a, miR-379, miR-139-5p and miR-200b-5p) as screening markers to segregate lung adenocarcinoma and granuloma patients, from healthy former smokers (AUC = 0.908; P < 0.001).…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
“…The ratio method used in our study was the same as that utilized by Boeri et al to develop diagnostic and prognostic miRNA signatures for lung cancer [17]. Boeri et al recently validated their miRNA signature in a large cohort of individuals with lung cancer [26], highlighting the potential for application in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA expression data values were then derived for all possible permutations of miRNA ratios within each individual. This ratio method was identical to that utilized by Boeri et al [17] in an analysis of data from individuals with lung cancer. Altogether 9900 miRNA ratios were obtained.…”
Section: Expression Profiling Of Circulating Mirnas To Identify a Mirmentioning
confidence: 99%
“…Another example is the involvement of microvesicle-contained serum miRNAs which mediate the signalling of angiogenesis and thus promote uncontrolled cell proliferation in glioblastoma [42]. Additionally, serum miRNAs are promising non-invasive biomarkers for diverse diagnostic applications such as for multiple sclerosis [43] or for cancers [44][45][46][47]. It has been proposed that different subtypes of glioblastoma can be distinguished by their unique serum miRNA signatures [48].…”
Section: Microrna Regulation In the Cnsmentioning
confidence: 99%